Clinical and serological comparison of 17 chronic progressive systemic sclerosis (PSS) and 17 CREST syndrome patients matched for sex, age, and disease duration. Issue 6 (December 1984) - Furst, D E; Clements, P J; Saab, M; Sterz, M G; Paulus, H E
Abstract : This study compares the clinical and serological differences between 17 PSS and 17 carefully matched CREST patients. Patients were matched for sex, age by decade, and, importantly, disease duration (11.2 +/- 9.2 vs. 12.0 +/- 9.3 years). Muscular and skin involvement were greater for the PSS groups (p less than 0.02) and pulmonary involvement was also greater (p less than 0.05), at least for non-smoking PSS patients. On the other hand no clinically significant differences were found between groups for other visceral involvement–including comparisons of gastrointestinal, cardiovascular, and renal involvement. There were also no laboratory differences except in anti-RNP antibody (p less than 0.04).